Causes and contrasts in current and past distribution of the white shark (Lamniformes: Carcharodon carcharias) off southeastern South America - Cione, Alberto Luis (2008)
The great white shark is a cosmopolitan temperate marine species which is rare in Argentina, Uruguay, and Brazil today. Several publications include the white shark as inhabiting Patagonian waters. However, there is no recent or fossil record of the white shark south of S 38°in-line 30′ in the southwestern Atlantic. A tooth found in Quaternary sediments at Pehuencó (S 38°in-line 56′), southern Buenos Aires province, is the southernmost occurrence of the species in the southwestern Atlantic. The occurrence of C. carcharias in the Buenos Aires province is another confirmation that the Argentine biogeographic province extends to the south of the Río de la Plata. The present extremely scarce record indicates that there are not permanent living populations in the South American Atlantic coast but occasional transient individuals. However, the abundant fossil and archaeological record suggests that it was much more common in southwestern Atlantic during the late Pleistocene and Holocene than today. This drop in abundance is here mostly attributed to the massive extermination of pinnipeds and cetaceans during the XIXth and XXth centuries. Patagonian waters, where marine mammals are relatively abundant even today, might be too cold for the species which is mostly encountered between 15-23°in-line C. Besides, another important predator, the killer whale, which also feeds on marine mammals, is frequently found in these waters. Consequently, available evidence suggests that unrestricted hunting of pinnipeds and cetaceans also decimated another animal, a fish.